Saberes escolares y estrategias interculturales en estudiantes y egresados del Instituto Intercultural Ñöñho - Mira Tapia, Alejandro (2017)
This article is based on a two-year ethnographic research that analyzes the process of professionalization and community work experiences of students and graduates of the Instituto Intercultural Ñöñho (IIÑ), a small indigenous university located in the ñöñho (otomí) region of the southern Mexican state of Querétaro. Among the main findings it presents that these actors collectively build and display a set of intercultural strategies (Bertely, 1997) to intervene in three issues: (i) the local socio-economic marginalization conditions, (ii) the cultural and language shift, (iii) and the violence within the socialization spaces of the youths.; all these through the sociocultural application of their academic knowledge. Firstly, this study puts in historical perspective the different paths of indigenous professionalization that have existed in the Mexican context. Subsequently, it offers a contextualization of the IIÑ and of the pedagogical profile of its degree program in Solidarity Economics. Finally, it describes the intercultural strategies produced by the students and graduates from this indigenous university, departing from the assertion of their own ethnicity within their schooling process.